Perilaku Pemilih Pada Pemilihan Gubernur dan Wakil Gubernur Provinsi Kalimantan Barat (Studi pada Anggota Dewan Adat Dayak) - Ira Patriani; Bernardo Eben Navire (Parabela: Jurnal Ilmu Pemerintahan & Politik Lokal, 2022)
This study examines the form of voting behavior of the Dayak community in the election of Governor and Deputy Governor of West Kalimantan in 2018. This type of research uses a qualitative descriptive method. The data collection technique is through interviews and documentation at the Dayak Customary Council. The research findings show that the voting behavior of the Dayak community tends to lead to primordial voters.